Die Organisation und Leitung der Arbeit Mit Audiovisuellen Lehr- und Lernmitteln an der Humboldt-Universität zu Berlin und an Anderen Hochschulen in der Ddr - Heun, Hans-Georg (Wydawnictwo Naukowe UAM w Poznaniu, 1991)
Heun Hans-Georg, Die Organisation und Ieitung der Arbeit mit audiovisuellen lehr- und Ißrnmitteln an der Humboldt-Universität zu Berlin und an anderen Hochschulen in der DDR (Organization and conducting of work with audiovidual aids at the Humboldt University and other schools of higher education in the German Democratic Republic), „Neodidagmata” XX, Poznan 1991, Adam Mickiewicz University Press, pp. 131-136. ISBN 83-232-0302-4. ISBN 0077-653X. Received: November 1987. Audiovisual aids have become now an indispensable help for teachers. The centre of audiovisual aids at the Humboldt University in Berlin performs the following tasks: a) production of audiovisual materials; b) technical service of classes and lectures and seminars and repairing of the equipment; c) information on new audiovisual aids and lending services; d) training of students and university teachers in operating audiovisual aids; e) studies on application of audiovisual aids in schools of higher education.
Keywords: materiały audiowizualne; audiovisual materials; Uniwersytet Humboldta; Humboldt University